1999
DOI: 10.1002/(sici)1097-4601(1999)31:8<577::aid-kin7>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of benzene decomposition near 1000 K: The effects of toluene impurity

Abstract: Kinetic data of Brooks et al. [3] on the decomposition of C 6 H 6 near 1000 K have been analyzed by computer modeling. The observed overall 3/2-order kinetics could be accounted for by a mechanism composed of 4 key reactions involving H atoms and C 6 H 5 radicals using recently acquired rate constants. However, the appearance of CH 4 and the enhanced H 2 yields could only be explained by invoking the reactions of ϳ0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Until now, all experimental and theoretical studies ,, have reported biphenyl as the only product of reactions and . Additionally, Manion et al has reported the rate constant for the reverse reaction (–1).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, all experimental and theoretical studies ,, have reported biphenyl as the only product of reactions and . Additionally, Manion et al has reported the rate constant for the reverse reaction (–1).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction kinetics of the C 6 H 5 radical with a wide variety of reactants have been investigated by cavity ringdown spectroscopy , and laser flash photolysis techniques . The reaction kinetics ,,, of phenyl with the diatomics: HBr, O 2 , NO, and H 2 , have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures, primary reactions of the pyrolysis of benzene are rather simple. 31 The only reaction of unimolecular initiation is the breaking of a C-H bond (bond energy of 110.9 kcal mol -1 ). Breaking of a benzylic C-C bond of benzene is very difficult because of the high energy of this type of bond (120.8 kcal mol -1 ).…”
Section: Discussionmentioning
confidence: 99%